Cooperation and Competition among Clustered MSEs in East Java - Hoetoro, Arif (Gadjah Mada International Journal of Business, 2014)
There has been a common picture in economic development that micro and small enterprises (MSEs) tend to conglomerate in various clusters for the sake of gaining location advantages. These MSEs then create inter-firm linkages and business strategies as the two play an important role in their performance. By taking selected manufacturing MSEs that operate in various small industrial clusters in East Java, Indonesia, this research examined the relationships between the inter-firm linkages and business strategies applied simultaneously by MSEs and their impacts on the firmâs performance. Viewed from the perspective of a co-opetition strategy, the results of this study revealed that some types of inter-firm linkages and business strategies matter for the MSEsâ performance. However, within small industrial clusters, inter-firm linkages seem to be less effective compared to business strategies in affecting a firmâs performance.Â Â Â Â